Past year questions: radiographic anatomy 2 - Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Hassan, Radhiana; Che Mohamed, Siti Kamariah; Abidin, Mohd Radhwan (Nazdee Resources, 2022)
This is a compilation of past year's questions prepared for Bachelor of Medical Imaging examination. The students are required to identify and discuss the anatomy of body parts related to the images shown using different imaging modalities. This book covers topic on abdomen, pelvis, upper limbs and lower limbs.